Linear and Nonlinear Polarization Syntheses and Their Programmable Controls based on Anisotropic Time‐Domain Digital Coding Metasurface. Issue 1 (11th January 2021) - Ke, Jun Chen; Dai, Jun Yan; Chen, Ming Zheng; Wang, Li; Zhang, Cheng; Tang, Wankai; Yang, Jin; Liu, Wei; Li, Xin; Lu, Yunfeng; Cheng, Qiang; Jin, Shi; et al.
Abstract : Polarization Synthesis A general polarization regulation scheme based on anisotropic time‐domain digital coding metasurface is proposed by Qiang Cheng, Shi Jin, Tie Jun Cui, and co‐workers in article number 2000060 . Both linear and nonlinear polarization syntheses and their real‐time programmable controls can be achieved, which offers a new approach to expand the scope of the polarization regulation. An anisotropic time‐domain digital coding metasurface is designed and fabricated to validate the feasibility of the proposed scheme. It is expected to find important applications in novel wireless communication and radar systems.